2022
DOI: 10.1038/s41522-022-00341-9
|View full text |Cite
|
Sign up to set email alerts
|

Impaired amino acid uptake leads to global metabolic imbalance of Candida albicans biofilms

Abstract: Candida albicans biofilm maturation is accompanied by enhanced expression of amino acid acquisition genes. Three state-of-the-art omics techniques were applied to detail the importance of active amino acid uptake during biofilm development. Comparative analyses of normoxic wild-type biofilms were performed under three metabolically challenging conditions: aging, hypoxia, and disabled amino acid uptake using a strain lacking the regulator of amino acid permeases Stp2. Aging-induced amino acid acquisition and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 71 publications
(90 reference statements)
2
4
0
Order By: Relevance
“…This relationship explains some of the interesting stp2 phenotypes that are relevant to C. albicans pathogenesis, such as the defective filamentation in the phagosomes of macrophages (Danhof & Lorenz, 2015; Vylkova & Lorenz, 2014) and virulence in murine systemic infection model (Amorim‐Vaz et al., 2015; Vylkova & Lorenz, 2014), which we have also shown to be dependent on proline catabolism (Silao et al., 2019, 2023). The data presented here also help explain other findings related to the increase in proline uptake in stp2 mutant (Bottcher et al., 2022), which is likely a compensatory mechanism to generate more energy when intracellular amino acids become limiting. The tight dependency of Gdh2 expression on Stp2 represented an apparent conundrum given that Gdh2 expression is extremely low in YPD (Silao et al., 2020) even though Stp2 is constitutively expressed and activated (Martinez & Ljungdahl, 2005; Miramon & Lorenz, 2016).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This relationship explains some of the interesting stp2 phenotypes that are relevant to C. albicans pathogenesis, such as the defective filamentation in the phagosomes of macrophages (Danhof & Lorenz, 2015; Vylkova & Lorenz, 2014) and virulence in murine systemic infection model (Amorim‐Vaz et al., 2015; Vylkova & Lorenz, 2014), which we have also shown to be dependent on proline catabolism (Silao et al., 2019, 2023). The data presented here also help explain other findings related to the increase in proline uptake in stp2 mutant (Bottcher et al., 2022), which is likely a compensatory mechanism to generate more energy when intracellular amino acids become limiting. The tight dependency of Gdh2 expression on Stp2 represented an apparent conundrum given that Gdh2 expression is extremely low in YPD (Silao et al., 2020) even though Stp2 is constitutively expressed and activated (Martinez & Ljungdahl, 2005; Miramon & Lorenz, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…The data presented here also help explain other findings related to the increase in proline uptake in stp2 mutant (Bottcher et al, 2022), which is likely a compensatory mechanism to generate more energy when intracellular amino acids become limiting.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The SPS plasma membrane sensor, comprised of the subunits Ssy1, Pr32 and Ssy5, activated in fungi upon sensing of extracellular amino acids results in proteolytic cleavage of the transcription factor Stp2 that controls amino acid permeases [ 55 ]. Spt2 has now been shown to have a central effect in biofilm formation, leading to a global metabolic imbalance, suggesting it could act as a key target alongside antifungal therapy [ 56 ]. In addition to biofilm formation, amino acid metabolism is associated with virulence and triggering of yeast to hyphae morphogenesis [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The less closely related species, Candida parapsilosis, Loderomyces elongisporus and Spathaspora passalidarum are also able to form biofilms, but these are structurally different and of lesser biomass than those of C. albicans [10][11][12][13][14]. Transcript profiling, proteome analyses and metabolomic studies of C. albicans planktonic and biofilm cells have shown that cellular differentiation and metabolic reprogramming are two critical events that occur when C. albicans cells transition from the planktonic to the biofilm growth mode [13,[15][16][17][18][19][20][21]. Studies on C. albicans transcription regulators have suggested that a well-coordinated crosstalk operates during biofilm development.…”
Section: Introductionmentioning
confidence: 99%